Clinical, morphological and immunohistochemical evidence that small‐cell carcinoma of the ovary of hypercalcaemic type (SCCOHT) may be a primitive germ‐cell neoplasm. Issue 7 (20th March 2017) - McCluggage, W Glenn; Witkowski, Leora; Clarke, Blaise A; Foulkes, William D
Abstract : Aims: The histogenesis and cell lineage of small‐cell carcinoma of the ovary of hypercalcaemic type (SCCOHT) is unknown. We aim to provide evidence that this may be a primitive germ‐cell neoplasm arising from a teratoma. Methods and results: Following the identification of two cases of SCCOHT associated with germ‐cell tumours (one dermoid cyst, one immature teratoma with a focus of yolk sac tumour), we undertook a literature review to look for any prior reports of SCCOHT in association with other neoplasms or elements. This revealed two cases associated with immature teratomas, one arising in an ovary where a cystectomy had been undertaken previously for a teratoma and another in association with a mucinous borderline tumour. Mucinous elements have also been reported in SCCOHT, this type of epithelium potentially being of teratomatous derivation. We stained whole tissue sections of nine cases of SCCOHT and a tissue microarray (TMA) containing 34 different SCCOHT with germ‐cell markers SALL4, OCT3/4, alpha fetoprotein (AFP) and glypican 3. All except one of the whole tissue sections and approximately half the TMA cases were positive with SALL4, while all cases were OCT3/4‐, AFP‐ and glypican 3‐negative, except for focal glypican 3 staining in an occasional case. Conclusions: Our findings provide additional evidence to that proposed by others that SCCOHT is a primitive germ‐cell neoplasm arising from a teratoma.